2017
DOI: 10.4084/mjhid.2017.013
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization in Patients With Sickle Cell Disease and Thalassaemia: Experience of Single Centre From Oman

Abstract: BackgroundBlood transfusion is an integral part of the supportive care for patients with sickle cell disease (SCD) and thalassaemia. The hazard of red cell alloimmunization, however, is one of the main complications of this therapy.ObjectivesThe aim of this study was to evaluate the prevalence of red cell alloimmunization in Omani patients with sickle cell anaemia and thalassemia.MethodsThis study included 262 patients whose historical transfusion records were available. One hundred and twenty-nine patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
4
7
4
Order By: Relevance
“…Of all alloantibodies detected, anti-K (33.3%) was the most frequent alloantibody followed by anti-E (22.2%), anti-D (11.1%), anti-C (11.1%), and anti-c (11.1%), respectively. Given that both Rh and Kell systems have highly immunogenic antigens and phenotype-matched RBC was not performed for these antigens except D, the prevalence of alloantibodies of both systems among our study subjects was similar to previous reports [ 9 , 10 , 13 16 , 19 ]. Donor RBC phenotyping for Rh (D, C, E, c, and e) and K 1 (partial phenotype matching) is necessary to avoid alloimmunization and stop unwanted clinical consequences in SCD patients [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Of all alloantibodies detected, anti-K (33.3%) was the most frequent alloantibody followed by anti-E (22.2%), anti-D (11.1%), anti-C (11.1%), and anti-c (11.1%), respectively. Given that both Rh and Kell systems have highly immunogenic antigens and phenotype-matched RBC was not performed for these antigens except D, the prevalence of alloantibodies of both systems among our study subjects was similar to previous reports [ 9 , 10 , 13 16 , 19 ]. Donor RBC phenotyping for Rh (D, C, E, c, and e) and K 1 (partial phenotype matching) is necessary to avoid alloimmunization and stop unwanted clinical consequences in SCD patients [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, this study aimed to investigate the frequency of alloimmunization among these patients. The rate of alloimmunization observed in the present study was 7.76%, which is lower than that reported in many studies of RBC alloimmunization in SCD patients [ 10 , 12 15 , 19 , 23 25 ]. Other studies present lower rates of RBC alloimmunization [ 16 , 26 – 28 ].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Observational studies conducted on random patients who received incidental transfusions demonstrated 1–3% alloimmunization. However, in patients with sickle cell disease (SCD) who receive chronic transfusions this can increase to 8% or even as high as 76% ( Campbell-Lee and Kittles, 2014 ; Alkindi et al, 2017 ). In severe cases the only option available for the patient is a stem cell transplantation, which carries significant risk on its own.…”
Section: Introductionmentioning
confidence: 99%